"Made Me Feel Connected": A Qualitative Comparative Analysis of Intimate Partner Violence Routine Screening Pathways to Impact. (March 2020) - Spangaro, Jo; Koziol-McLain, Jane; Rutherford, Alison; Zwi, Anthony B.
Intimate partner violence (IPV) routine screening is widely implemented, yet the evidence for pathways to impact remains unclear. Of the 32 abused women interviewed 16 weeks after antenatal IPV screening, 24 reported positive impact, six reported nil positive impact, and two reported negative impact. Using qualitative comparative analysis (QCA), key conditions for positive impact were care in asking, and support and validation from the midwife. Lack of these and lack of continuity of care were relevant to nil positive impact. Benefits included naming the abuse, connection, unburdening, taking steps to safety, and enabling informed care. Disclosure was not required for positive impact.